Collected travel writings : - James, Henry (The Library of America, 1993)
Henry James' travel writings on France and Italy are a case study in fine arts perception, understanding and interpretation. He treats each new locale as a new horizon to be engaged, absorbed, and internalized through a hermeneutic of analogical interiority. Roaming within the halls and chambers of French and Italian architecture opens, through the text, new conduits for an understanding of the vast interiority that exists within the self-examining-self. James is a master at relating the space of each location with the thoughts, instincts, relational perceptions and education of the observer